2020
DOI: 10.1186/s12885-020-06920-3
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of acquired resistance to reversible versus irreversible EGFR tyrosine kinase inhibitors

Abstract: Background: Over the past years, EGFR tyrosine kinase inhibitors (TKI) revolutionized treatment response. 1stgeneration (reversible) EGFR TKI and later the 2nd-generation irreversible EGFR TKI Afatinib were aimed to improve treatment response. Nevertheless, diverse resistance mechanisms develop within the first year of therapy. Here, we evaluate the prevalence of acquired resistance mechanisms towards reversible and irreversible EGFR TKI. Methods: Rebiopsies of patients after progression to EGFR TKI therapy (>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
(51 reference statements)
1
14
0
Order By: Relevance
“…In the analysis of previous large cohort studies, the acquired EGFR-T790M mutation rate was higher in NSCLC patients taking first-generation EGFR-TKIs (gefitinib and erlotinib) than in those taking the second-generation EGFR-TKI afatinib. 42 , 43 The secondary EGFR-T790M mutation rates in our study were similar to those in previous cohort studies, and our results indicated that the addition of bevacizumab to first- and second-generation EGFR-TKIs did not affect the frequency or the trend of acquired EGFR-T790M mutation after disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…In the analysis of previous large cohort studies, the acquired EGFR-T790M mutation rate was higher in NSCLC patients taking first-generation EGFR-TKIs (gefitinib and erlotinib) than in those taking the second-generation EGFR-TKI afatinib. 42 , 43 The secondary EGFR-T790M mutation rates in our study were similar to those in previous cohort studies, and our results indicated that the addition of bevacizumab to first- and second-generation EGFR-TKIs did not affect the frequency or the trend of acquired EGFR-T790M mutation after disease progression.…”
Section: Discussionsupporting
confidence: 89%
“…After removing duplicate studies and excluding titles and abstracts, 56 studies were considered for full-text evaluation, and 27 studies were excluded for different reasons (Table S3). Finally, 29 studies [including 23 multi-cohort studies (5,11, and six single-cohort studies (43)(44)(45)(46)(47)(48)] were included in the risk of bias assessment and singlearm meta-analysis, and 20 multi-cohort studies were included in the network meta-analysis. Among the studies identified in the search results, acquired T790M acquisition rates after treatment with gefitinib, erlotinib, icotinib, or afatinib were noted.…”
Section: Study Identificationmentioning
confidence: 99%
“…The main resistance mechanism of EGFR-TKIs is the emergence of secondary EGFR-T790M mutations. Among the first-/second-generation EGFR-TKIs-resistant patients, 50% of patients have secondary EGFR-T790M mutations (13)(14)(15). Repeated biopsy cohort studies have shown that approximately 3%-10% of acquired EGFR-TKIs resistance is related to histological transformation to SCLC (16,17).…”
Section: Introductionmentioning
confidence: 99%